Isolation and culture of primary osteocytes from the long bones of skeletally mature and aged mice. (June 2012) - Stern, Amber Rath; Stern, Matthew M.; Van Dyke, Mark E.; Jähn, Katharina; Prideaux, Matthew; Bonewald, Lynda F.
The purpose of this work was to establish a methodology to enable the isolation and study of osteocytes from skeletally mature young (4-month-old) and old (22-month-old) mice. The location of osteocytes deep within bone is ideal for their function as mechanosensors. However, this location makes the observation and study of osteocytes in vivo technically difficult. Osteocytes were isolated from murine long bones through a process of extended collagenase digestions combined with EDTA-based decalcification. A tissue homogenizer was used to reduce the remaining bone fragments to a suspension of bone particles, which were placed in culture to yield an outgrowth of osteocyte-like cells. All of the cells obtained from this outgrowth that displayed an osteocyte-like morphology stained positive for the osteocyte marker E11/GP38. The osteocyte phenotype was further confirmed by a lack of staining for alkaline phosphatase and the absence of collagen1a1 expression. The outgrowth of osteocytes also expressed additional osteocyte-specific genes such as Sost and Mepe . This technique facilitates the isolation of osteocytes from skeletally mature bone. This novel enabling methodology should prove useful in advancing our understanding of the roles mature osteocytes play in bone health and disease.